Natural Gas in Europe : The Potential Impact of Disruptions to Supply - Di Bella, Gabriel; Flanagan, Mark.; Foda, Karim; Maslova, Svitlana (Washington, D.C. : International Monetary Fund, 2022)
This paper analyzes the implications of disruptions in Russian gas for Europe's balances and economic output. Alternative sources could replace up to 70 percent of Russian gas, allowing Europe to avoid shortages during a temporary disruption of around 6 months. However, a longer full shut-off of Russian gas to the whole of Europe would likely interact with infrastructure bottlenecks to produce very high prices and significant shortages in some countries, with parts of Central and Eastern Europe most vulnerable. With natural gas an important input in production, the capacity of the economy would shrink. Our findings suggest that in the short term, the most vulnerable countries in Central and Eastern Europe - Hungary, Slovak Republic and Czechia - face a risk of shortages of as much as 40 percent of gas consumption and of gross domestic product shrinking by up to 6 percent. The effects on Austria, Germany and Italy would also be significant, but would depend on the exact nature of remaining bottlenecks at the time of the shutoff and consequently the ability of the market to adjust. Many other countries are unlikely to face such constraints and the impact on GDP would be moderate-possibly under 1 percent. Immediate policy priorities center on actions to mitigate impacts, including to eliminate constraints to a more integrated gas market via easing infrastructure bottlenecks, to accelerate efforts in defining and agreeing solidarity contributions, and to promote stronger pricing pass through and other measures to generate greater energy savings. National responses and RePowerEU contains many important measures to help address these challenges, but immediate coordinated action is called for, with specific opportunities in each of these areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Conflicts; Macroeconomics; Negotiations; Sanctions